Flow Cytometric Assessment of AKT Signaling in Platelet Activation: An Alternative Diagnostic Tool for Small Volumes of Blood - Althaus, K.; Wagner, M.; Marini, I.; Bakchoul, T.; Pelzl, L. (Hämostaseologie, 2020)
Introduction The diagnosis of platelet function disorder in children is challenging. Light transmission aggregometry is the gold standard for platelet function disorders. However, large blood volumes are required. Currently, there are no existing tools for the diagnosis of platelet function disorders that use small blood volumes. AKT signaling plays a central role in platelet activation during hemostasis and might be visualized by flow cytometry.Methods Platelet-rich plasma obtained by centrifugation of citrated blood from healthy volunteers was activated with arachidonic acid, thrombin receptor activating peptide-6 (TRAP-6), collagen, adenosine diphosphate ADP, collagen-related peptide (CRP), and epinephrine. After platelet activation, the phosphorylation of AKT was assessed by flow cytometer using a Navios cytometer.Results Healthy volunteers showed a reproducible phosphorylation of AKT upon activation. In comparison to nonactivated platelets, we documented an increase in pAKT expression with all agonists. Especially TRAP-6 and CRP caused considerable increase in percentage of pAKT expression throughout all the tested healthy volunteers.Conclusion An activation of the AKT-signal pathway by different agonists can clearly be detected on the flow cytometer, indicating that the visualization of signaling in platelets by flow cytometry might be an efficient alternative for light transmission aggregometry to test platelet function in children.
Keywords: AKT; platelet; acquired platelet disorders; inherited platelet disorders; platelet function